Aplikasi Limbah Cair Pabrik terhadap Keharaan Tanah dan Tanaman serta Pengaruhnya terhadap Produksi Kelapa Sawit di Tanah Pasiran - Gunawan, Sri; Hidayat, Wahyu; Purwoto, Harsunu; Wirianata, Herry; Renjani, Rengga Arnalis (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2024)
Management of sandy soil in oil palm plantations requires location-specific technology that prioritizes sustainability principles. Palm oil mill Effluent (POME) has the potential to be a substitute for nutrients for oil palm plantations. This research aims to reveal the role of POME in improving soil and tissue nutrient status and increasing oil palm production on sandy soil. The research was conducted on eleven plantation blocks using POME and six blocks without by-products (30 ha block-1, sandy soil) of 12-13 years palm. Observations were carried out for 3 years, including harvest tonnage, number and weight of fresh fruit bunches (FFB) of palm oil, soil, and tissue nutrient content (N, P, K, Mg, Ca, Cu, and B), CEC, and soil organic carbon. The research results show that POME flatbed system application can increase the nutrient content, pH, CEC, and soil organic carbon in the low to medium range. This application can also increase the tissue nutrient content to the optimal range. Production, quantity, and weight of oil palm FFB on sandy soil applied by POME were increased compared to those without by-product application. This application can also reduce monthly fluctuations in palm oil production on sandy soil.